Sino-Russian Coexistence in Serbia: Strategic Symmetry - Mirela Imsirovic; Adnan Kapo; Georges Olemanu Lohalo; Eliza Farahdiba Saleh (Jurnal Politik Profetik, 2024)
In recent decades, China has significantly increased its global economic presence, emerging as one of the leading powers in the international system, in alignment with its strategic plan through 2049. This presence includes a keen interest in Southeast Europe, with Serbia identified as a key strategic partner. China’s approach to Serbia intersects with Russia’s longstanding presence rooted in the historical and cultural ties with Serbia. This paper examines the strategic interests and goals of China and Russia in Serbia, exploring their respective methods and tools. It also delves into Serbia’s foreign policy aspirations for sustainable security trying to balance the presence of superpowers within, and around its territory. The paper evaluates Serbia’s try of strategic navigation of its geostrategic position between East and West, questioning if Serbia is actually naive or aware of its circumstances. The study elucidates on how China and Russia’s strategic maneuvers in the region, often subconsciously, shape Serbia and its neighboring countries. Within this intricate landscape, the concept of “Strategic symmetry” emerges as a crucial element, highlighting the delicate balance of influence that both powers exert in Serbia while it strives to maintain its entry into the European Union.